Mathematical models for the parameters of data flows in information and telecommunication networks - Косенко, Віктор Васильович; Бугас, Дмитро Миколаевич (Eastern-European Journal of Enterprise Technologies, 2015)
This paper analyzes and mathematically models the parameters of data flows in the information and telecommunications network. The fluctuation in the data flows, which is inherent in modern multiservice systems, does not allow designing a system based solely on the average bandwidth indices. It is necessary to determine the parameters of the flows of data generated by the tasks performed in the network nodes, which requires devising mathematical models that would reflect both the information and the technical structures of the network. We have determined the structure of the mathematical apparatus for analyzing the network structure in the form of a complex mathematical model that describes the information structure, the data flows between the nodes and the technical structure of the network. The study describes basic parameters of the model of the network information structure, which lays the basis for modeling the data flows. The model parameters characterize the intensity of the data flows between the network nodes in performing the applied tasks and the queries of the user. The devised mathematical model describes the parameters of the data flows between the network nodes in the fixed information structure and takes into account both the exchange of data between the nodes, which results from the interaction of applications in separate nodes, and the user queries to the data stores. We have devised a mathematical model of the data flows in a stratified multi-tier information structure of the network that is typical of the most common modern technologies of the network construction. The model allows determining the loading capacity of the network channels and the network equipment while designing the technical structure of the network. The suggested models can be applied in devising the methods and detailed algorithms for managing the data flows in a specialized network.